Are CEOs incentivized to avoid Corporate Taxes? - Empirical Evidence on Managerial Bonus Contracts - Heiner Schmittdiel (Tinbergen Institute, 2014)
In this paper, we test empirically whether there is a relationship between corporate income taxes and CEO bonus payments. Using Compustat and ExecuComp data from 1992 to 2010, we find mixed results. Looking at the whole sample, the average bonus contract rewards tax savings excessively in comparison to other determinants of corporate net income. A possible explanation is that managers require to be compensated for the additional risk inherent in running an aggressive tax strategy. In accordance with previous literature, we document a substantial heterogeneity in compensation practices across industries. It appears that our main result is driven by firms in the Industrial and Retail sectors. We further find that companies with greater tax planning opportunities, for example by virtue of size or operations abroad, are more likely to condition the CEOs bonus on corporate income taxes.
Keywords: H25; H26; M41; M52; 330; CEO incentives; executive compensation; tax avoidance